FEATURES OF PROGRAM-CONTENT ASSISTANCE FOR THE DEVELOPMENT OF SELF-EDUCATION COMPETENCE IN BACHELOR'S STUDENTS - N. Romaeva; O. Sal'nikova (Вестник Северо-Кавказского федерального университета)
The article describes the elements of program-content assistance for the development of self-education competence in bachelor's students. The characteristic of the competence of education is given, and shown that it can be formed through the implementation ofpedagogical features within the framework of the corresponding program-content assistance. The article reveals the idea that the specifics ofprogram-content assistance for the development of self-education competence is associated with the designation of the place and signiicance of this competence, the deinition of its descriptors, depending on the planned basic and advanced levels. The developed example of educational competence formation indicators for a speciic discipline is presented.